Physiological, morphological characteristics and blood profile of female elite Brazilian soccer players according to position - Santos Silva, Paulo; Pedrinelli, Andre; B. Osorio, Bruna; Aquino, Thais P.; D’A Greve, Julia Maria; Hernandez, Arnaldo Jose; Veiga Guimaraes, Guilherme (Open Science Journal, 2021)
The main goal of this study was to identify the performance parameters and blood profile found among female soccer players. The second aim was to examine if there were any systematic differences between players assigned to different playing positions. Thirty-six players (age: 23.7 ± 3.5 y; weight: 61.9 ± 5.7 kg; height: 165.7± 6.2 cm) underwent a set of laboratory tests (cardiopulmonary exercise test, skinfold measurements, Wingate test, sit-and-reach test, and blood biochemical tests). The following results were verified: maximal oxygen uptake (53±3.9 mL.kg-1.min-1), second ventilatory threshold (11.5 ± 0.8 km.h-1), body fat (14.1 ± 2.9%), Wingate anaerobic test (peak power: 9.5 ± 0.8 w.kg-1; mean power: 7.3 ± 0.4 w.kg-1 and fatigue index: 55.5 ± 4.9%), flexibility test [sit-and-reach] (18.1 ± 2.9 cm) and biochemical parameters of blood (Hb:13.9 ± 0.3 g.dL-1; iron: 85.2 ± 12.6 µ.dL-1; calcium: 9.2±0.5 mg.dL-1; total cholesterol: 204.7 ± 34.7 mg.dL-1; HDL-c: 50.7± 3.6 mg.dL-1; LDL-c: 125.8± 23.3 mg.dL-1; triglycerides: 96.8±18.5 mg.dL-1). In conclusion, the current results indicate that present elite players' physiological characteristics are similar to those previously shown, despite the rapid changes of the female soccer game worldwide. However, data showed that different playing positions had different physiological and anthropometrics differences.